Implementasi Khiyar Majelis Dalam Akad Transaksi Jual Beli Perspektif Ekonomi Syariah - Jamaluddin, Jamaluddin; Sahib, Munawwarah; Kasim, Sinta (Fakultas Agama Islam Universitas Cokroaminoto Makassar, 2023)
This study aims to analyze one of the rights contained in the sale and purchase transaction, namely the khiyar right. The type of research used is library research. There are two approaches used, namely the normative theological approach and the socio-economic approach. Information on data sources is obtained from primary data and secondary data with data collection methods carried out by in-depth searches of references and then analyzed comprehensively. The results showed that in the perspective of Sharia economics, khiyar is one of the rights that must be given to both parties in buying and selling transactions, but the current phenomenon is very rarely found to be implemented by both parties in the transaction. Therefore, one of the findings in this study is to provide education to the public about the importance of implementing khiyar as an integral part of buying and selling, so that both parties like each other.